A bio-injectable algin-aminocaproic acid thixogel with tri-stimuli responsiveness. (1st January 2016) - Chejara, Dharmesh R.; Mabrouk, Mostafa; Badhe, Ravindra V.; Mulla, Jameel A.S.; Kumar, Pradeep; Choonara, Yahya E.; du Toit, Lisa C.; Pillay, Viness
Highlights: Algin-aminocaproic acid based novel bio-injectable thixogel was synthesized. Designed thixogel exhibited tri-stimuli responsiveness with applied stimuli. Thixogels may have potential application in bio-medical applications. Abstract: In this article a novel bio-injectable algin-aminocaproic acid (Alg-ACA) tri-stimuli responsive thixogel system is reported. The designed soft thixotrophic hydrogel (thixogel) was characterized using various analytical techniques such as FT-IR, NMR, SEM, AFM and DSC. The soft thixogel system was further investigated for stress responsiveness using different rheological studies which confirmed the thixotropic nature of the gel [Thixotropic area ( A r ) of Alg-ACA (1:0.5), Alg-ACA (1:1) and Alg-ACA (1:2), were 23.5%, 43.1%, and 27.59%, respectively, which were higher than that of Na-Alg (2.08%)]. The thixogel also demonstrated temperature and ultrasonication responsiveness. This tri-stimuli responsive soft thixogel system was rendered flowable (fluid) on applying the described physical stimuli and recovered its "rigid" gel structure upon removal of the applied stimuli. This approach of synthesizing a thixogels may be applicable to a broad variety of other natural polymers and has the potential for use in biomedical applications.